Physical representation of hillslope leaky barriers in 2D hydraulic models: A case study from the Calder Valley. Issue 3 (27th May 2022) - Senior, Jake G.; Trigg, Mark A.; Willis, Thomas
Abstract: The resources of small‐scale community‐based flood risk action groups are often limited, hence studies to model and predict the effects of Natural Flood Management are often restrained by time and lack of empirical data to validate results. As a result, representations of hillslope leaky barriers are largely modelled as several equifinal approaches, often without survey data. The geometrical characteristics of hillslope leaky barriers were surveyed for the first time at Hardcastle Crags, Calder Valley. This data informed six 2D hydraulic model representation scenarios with varying combinations of topography modification and roughness increase, allowing the sensitivity of their results to be tested. Results from Scenario 3 (topography modification and roughness increase) estimated total hillslope runoff peak flow to reduce by 16.6% in a 1:1‐year design return period; however, this reduction diminished as rainfall intensity increased. Return periods of over 1:30 year estimated peak flow reductions of <5%. Only 14.3%–21.7% (98–148 m 3 ) of the total additional storage provided by the barriers is mobilised during simulated events. A multi‐peaked rainfall event from December 2015 was also simulated. Although the initial peak flow was reduced by 22.7%, as storage became mobilised, effectiveness reduced significantly for subsequent peaks within the same event.